2016
DOI: 10.1074/jbc.m116.749341
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like Kinase 1 Regulates Vimentin Phosphorylation at Ser-56 and Contraction in Smooth Muscle

Abstract: Polo-like kinase 1 (Plk1) is a serine/threonine-protein kinase that has been implicated in mitosis, cytokinesis, and smooth muscle cell proliferation. The role of Plk1 in smooth muscle contraction has not been investigated. Here, stimulation with acetylcholine induced Plk1 phosphorylation at Thr-210 (an indication of Plk1 activation) in smooth muscle. Contractile stimulation also activated Plk1 in live smooth muscle cells as evidenced by changes in fluorescence resonance energy transfer signal of a Plk1 sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 47 publications
0
89
0
Order By: Relevance
“…External stimulation induces vimentin phosphorylation at Ser-56, which leads to reorganization of the vimentin network, facilitating mechanical force transduction in smooth muscle. Vimentin phosphorylation at Ser-56 is catalyzed by p21-activated kinase 1 (PAK1) and polo-like kinase 1 (Plk1) in smooth muscle [50, 52, 67, 68]. Vimentin dephosphorylation at this residue is regulated protein phosphatase 1 in smooth muscle [49] (Fig.…”
Section: Role Of Intermediate Filaments In Cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…External stimulation induces vimentin phosphorylation at Ser-56, which leads to reorganization of the vimentin network, facilitating mechanical force transduction in smooth muscle. Vimentin phosphorylation at Ser-56 is catalyzed by p21-activated kinase 1 (PAK1) and polo-like kinase 1 (Plk1) in smooth muscle [50, 52, 67, 68]. Vimentin dephosphorylation at this residue is regulated protein phosphatase 1 in smooth muscle [49] (Fig.…”
Section: Role Of Intermediate Filaments In Cell Migrationmentioning
confidence: 99%
“…First, vimentin phosphorylation at Ser-56 by PAK1 and Plk1 leads to its disassembly in smooth muscle, which results in the release of CAS from cytoskeletal vimentin. CAS translocates to the cell cortex and promotes the Arp2/3 complex-mediated actin polymerization and branching, and lamellipodial formation [2, 34, 35, 50, 52, 65, 67, 74] (Fig. 4b).…”
Section: Role Of Intermediate Filaments In Cell Migrationmentioning
confidence: 99%
“…Plk1 further phosphorylates vimentin at S82 (Oguri et al , ; Yamaguchi et al , ), which regulates vimentin filament segregation, coordinately with rho‐kinase and Aurora‐B (Yamaguchi et al , ). Recently, another study also demonstrated that Plk1 regulates smooth muscle contraction by modulating vimentin phosphorylation at S56 (Li et al , ). In addition, Plk1 regulates cell surface levels of β1‐integrin and invasion by phosphorylating vimentin in breast cancer cells (Rizki et al , ).…”
Section: Discussionmentioning
confidence: 97%
“…Human airway smooth muscle (HASM) cells were previously described by our laboratory [ 11 14 , 28 ]. This study was approved by the Albany Medical College Committee on Research Involving Human Subjects.…”
Section: Methodsmentioning
confidence: 99%
“…A pool of globular actin (G-actin) is added to existing filamentous actin (F-actin) in response to contractile stimulation, which promotes contraction by enhancing the transmission of force between the contractile units and the extracellular matrix [ 4 , 6 10 ]. Thus, myosin can be viewed as an “engine” and the actin cytoskeleton as a “transmission system” for smooth muscle contraction [ 4 , 11 14 ]. Although myosin activation has been extensively investigated [ 1 , 2 ], the cellular processes that orchestrate actin polymerization are incompletely elucidated.…”
Section: Introductionmentioning
confidence: 99%